Pengendalian Infeksi Bakteri Aeromonas hydrophila pada Ikan Nila (Oreochromis niloticus) dengan Ekstrak Rimpang Lengkuas Merah (Alpinia purpurata) - Endang T.P. Sari; Tri Gunaedi; Ervina Indrayani (Jurusan Biologi FMIPA Universitas Cenderawasih, 2017)
MAS diseases (Motile Aeromonas Septicaemia) is caused by the bacterium Aeromonas hydrophila. One of the natural ingredients that can be used as an alternative to inhibit bacterial activity is the extract of red galangal rhizome (Alpinia purpurata). Active substances possessed of this material have potential as antibacterial. The purpose of this study is to determine the effectiveness of red galangal rhizome extract in the control of MAS disease in tilapia. The type of this research is experimental research in Completely Random Design (RAL) with 6 treatments, which are positive control, negative control, 250, 500, 750, and 1000 ppm. The result of the research on the activity of the galangal extract bacteria on A. hydrophila obtained the widest clear zone at 1000 ppm constipation, which is 9.7625 mm. The treatment has been conducted by immersion of Tilapia fish into the extracted red galangan rgizomes for 5 minutes, then it was put into aquarium for maintenance for 7 days. 0.1 ml A. hydrophila (108 cfu/ml) was injected to Tilapia. The result of the research on antibacterial shoes the wides clear zone at 1000 ppm with constipation, which is 9.7625 mm and the effectiveness test of red galangal extract on tilapia infected by A. hydrophila bacteria experience (ulcer) healing after 7 days with the concentration of rhizome extract of galangal 1000 ppm. Key words: red galangal rhizome extract, A. hydrophila, A. purpurata.